Penguatan Kompetensi Para Pendamping Iman Anak Kevikepan Semarang - Anselmus Djoko Prayitno; Hartutik Hartutik; FX Sugiyana; Andarweni Astuti; Nerita Setiyaningtiyas (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
PIA assistants need to have competence in outlining activity designs in the context of Catholic children's faith mentoring based on the Liturgical Year. This PkM activity raises the Gospel of Mark as an inspiration for children's faith mentoring activities. Therefore, this PkM activity comprehensively details 10 activity topics that cover various aspects of the Gospel of Mark, ensuring that each activity is in accordance with the specificities of the Liturgical Year and the ecclesiastical calendar. Each activity topic not only touches on subject matter relevant to the content of the Gospel of Mark, but also utilizes interactive and participatory learning methods such as group discussions, role simulations, and case analysis to actively engage children. Media is also a key component in this design, utilizing various learning tools such as multimedia presentations, documentary videos, audio recordings, and educational posters. This approach not only increased the attractiveness of the activity, but also provided variety in the learning approach, accounting for the diverse learning styles among participants. The main objective of this activity is to provide a holistic approach to mentoring children's faith. The emphasis is not only on theoretical understanding, but also involves the appreciation and application of the teachings of faith in children's daily lives.